Niemann-Pick Disease, Type A: Clinical Case of 5 Months Old Patient - Nataliya V. Zhurkova; Nato V. Vashakmadze; Andrey N. Surkov; Tatiana V. Turti; Kristina V. Bogdanova; Yuliya Yu. Kotalevskaya; Ekaterina Yu. Zakharova; Leyla S. Namazova-Baranova ("Paediatrician" Publishers LLC, 2024)
Background. Niemann-Pick disease, type A is a rare hereditary disease from the group of lysosomal storage diseases, it is characterized by early onset and progressive course. Description of this disease's clinical cases is crucial for early diagnosis and adequate management due to its rarity, rapid progression, and the development of new pathogenetic therapy methods.Clinical case description. The disease manifested on the second month of the patient's life with poor weight gain, frequent pneumonia, hepatosplenomegaly, diffuse muscular hypotonia, delayed motor development, and progressive neurological symptoms. Laboratory testing has revealed significant decrease in sphingomyelinase activity in blood. The heterozygous deletion c.996del in exon 2 of the SMPD1 gene has been revealed via direct automatic sequencing; it leads to frameshifting p.F333Sfs*52 (inherited from mother). Moreover, the previously described pathogenic nucleotide variant c.1252C>T (heterozygous) has been revealed in exon 3 of the SMPD1 gene; it leads to translation arrest p.Arg418* (inherited from father). Cherry-red spots were diagnosed at fundospcopy. The diagnosis of Niemann-Pick disease, type А was established according to clinical signs and molecular genetic testing results.Conclusion. The detection of physical and motor development delay, diffuse muscular hypotonia, hepatosplenomegaly, cherry-red spots at ophthalmological examination, lung involvement, recurrent pneumonia, and progressive neurological symptoms in a child during the first months of life indicates that this patient has Niemann-Pick disease, type А. Early molecular genetic testing is crucial for timely choosing the management approach and further genetic counselling of the family.